Preferences of US, EU, Honduran, and Chinese undergraduates for cloning - Anderson, Shonda Renee (Kansas State University, 2011)
The concept of animal cloning was first introduced to the public’s attention in 1996 with the birth of “Dolly the Sheep,” the first mammal to be cloned. Now, after more than a decade the technology has reached a point of feasibility on a commercial scale. With the publication of the U.S. Food and Drug Administration risk assessment on animal cloning in 2008, a report that concluded that the technology was safe and posed no risk to consumers, the issue has received renewed attention. In this thesis I use survey data to examine attitudes to the use of cloning in animal food production among samples of college students in the U.S., Ireland, France, Honduras, and China. Stated likelihood of consuming meat products from cloned animals is correlated with individual characteristics including socio-demographic variables (gender, and farming background) and attitudinal variables measuring concern about various food technologies. In addition, using ordered logit modeling, we examine how respondents might change their probability of consuming cloned products after being provided with information about scientific assessments about the safety of cloning and possible price reductions for cloned products. The analysis shows that: a) respondents in the U.S. and Honduras were more likely than those in other countries to indicate that they would consume cloned products, b) on average, respondents in all countries increased their stated likelihood of consuming cloned products when informed that the U.S. Food and Drug Administration and the European Food Safety Authority had assessed cloned foods as safe for human consumption, and c) individuals who were opposed to cloning on moral grounds were significantly less likely to consume cloned product and furthermore were less likely to respond positively to information about the safety of cloning.
Keywords: animal cloning; cloned products; biotechnology; food safety; food issues; consumer perception; Agriculture, General (0473); Economics, Agricultural (0503); Public Policy and Social Welfare (0630)